The Influence of Digitalization on Economic Growth by Mediation of Increasing the Productivity of MSME in the Culinary Field in Purwakarta Regency - Imroatussolehah, Suci; Efitasari, Nesti; Nopiyanti, Putri; Habibah, Nur (International Journal of Law Social Sciences and Management, 2024)
The use of digitalization (e-commerce and social media) can increase the productivity of MSME on economic growth in Purwakarta Regency. This study aims to determine whether digitalization mediates the increase in MSME productivity on economic growth in Purwakarta Regency. This research uses quantitative research methods with data collection techniques using questionnaires, and literature studies. The sample used in this study is culinary MSME that have used digitalization, with a total sample size of 100 MSME. Data processing techniques using smartPLS 3.0. The results showed that digitalization mediates the increase in MSME productivity on economic growth in Purwakarta Regency. Digitalization can affect economic growth through mediating increased productivity of MSME because MSME players can take advantage of digitalization as a medium for online promotion so that their products are better known and can increase sales, so that production targets are achieved. Thus, business profits will increase economic growth in Purwakarta Regency. This research contributes especially in the field of digitalization that can have an economic influence in Purwakarta Regency. Especially for umkm actors in the culinary field. The results of this research are literature that can help increase productivity in MSME.